Enhancing Crew Protection in Indonesian Commercial Fishing: A Critical Evaluation of ILO Convention 188 - Dewi, Dinda Mangesti; Prakarsa, Satria Unggul Wicaksana (Universitas Negeri Semarang, 2023)
This paper critically examines the efficacy of International Labour Organization (ILO) Convention 188 in protecting the rights and welfare of Indonesian fisherfolk engaged in commercial fishing activities. Indonesia, with its vast maritime territory and significant dependence on the fisheries sector, faces multifaceted challenges in ensuring the well-being of its fisherfolk amidst the complexities of the global fishing industry. By reviewing the provisions of Convention 188 and its implementation in the Indonesian context, this study sheds light on the gaps and shortcomings in safeguarding the rights, safety, and working conditions of Indonesian fishers. Moreover, it explores the socio-economic factors influencing the vulnerability of fisherfolk to exploitation and abuse, such as poverty, lack of education, and inadequate regulatory enforcement. Through an analysis of case studies and empirical data, this paper offers insights into potential strategies for enhancing the effectiveness of Convention 188 in protecting Indonesian fisherfolk, including improved enforcement mechanisms, capacity building initiatives, and greater collaboration between government agencies, civil society organizations, and the fishing industry stakeholders. Ultimately, the findings underscore the urgent need for comprehensive reforms and concerted efforts at the national and international levels to ensure the rights and well-being of Indonesian fisherfolk are upheld in the context of commercial fishing.